2012
DOI: 10.1109/lpt.2012.2185689
|View full text |Cite
|
Sign up to set email alerts
|

${\rm In}_{0.75}{\rm Ga}_{0.25}{\rm As}/{\rm InP}$ Multiple Quantum-Well Discrete-Mode Laser Diode Emitting at 2 $\mu{\rm m}$

Abstract: A discrete-mode laser diode fabricated in the InGaAs/InP multiple quantum-well system and emitting single mode at λ = 2 μm is reported. The laser had an ex-facet output power >5 mW at 25°C and the laser operated mode-hop free in the temperature range −5°C-55°C.Index Terms-Mid-infrared sources, semiconductor laser, single-mode laser, strained quantum-well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…The transmitter consisted of four directly modulated (1967.6, 1977.8, 1986.9, and 1992.5 nm) lasers and another four externally modulated (1995.7, 1998.4, 2001.9, and 2003.9 nm) channels. The lasers used were based on highly strained In 0.75 Ga 0.25 As multiple quantum well, ridge waveguide laser diode structures grown on InP substrates and designed for single mode operation at these wavelengths [10]. In order to directly modulate the lasers at the highest baud rate possible, S 21 frequency response was analyzed for each laser depending on the bias current.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmitter consisted of four directly modulated (1967.6, 1977.8, 1986.9, and 1992.5 nm) lasers and another four externally modulated (1995.7, 1998.4, 2001.9, and 2003.9 nm) channels. The lasers used were based on highly strained In 0.75 Ga 0.25 As multiple quantum well, ridge waveguide laser diode structures grown on InP substrates and designed for single mode operation at these wavelengths [10]. In order to directly modulate the lasers at the highest baud rate possible, S 21 frequency response was analyzed for each laser depending on the bias current.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Thulium-doped fiber amplifiers (TDFA) which operate over a wide bandwidth spanning from ~1.80 µm to 2.05 µm are also available at this waveband [9] and their use in a transmission experiment has been demonstrated [5]. Moreover, the increasing availability of telecommunication-grade optical components at 2 µm, such as lasers [10], modulators and photo-detectors (PD) [11], are making transmission experiments at 2 µm practical. We previously presented in [4] that either direct laser modulation, or external modulation can be implemented in the 2 µm region, and successfully demonstrated the first WDM transmission experiment over 290 m of HC-PBGF.…”
Section: Introductionmentioning
confidence: 99%
“…The master laser was an In0.75Ga0.25As multiple quantum-well discrete-mode laser diode [13] with inbuilt dual-stage isolator emitting 3 dBm of CW light at 2003.4 nm. In our experiments we found that the highest back-to-back capacity required slightly larger master laser power (7-8 dBm).…”
Section: Transmission Experiments Setupmentioning
confidence: 99%
“…Key components such as narrow linewidth lasers [13], external modulators, optical hybrids [14], high-speed photo detectors [15], as well as many passive components have already been developed for 2 µm region. With the availability of these building blocks, 2 µm fiber transmission systems have now been demonstrated and the transmission capacity has been consistently improved, although all experiments to date have been limited to simple data coding only.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows an operational diagram of the proposed approach; some minor details are omitted for clarity. A 1.654 µm narrow-linewidth fiber-coupled discrete-mode (DM) laser is employed, whose salient features are detailed in [35] for a similar device operating at 2 µm. The modulation characteristics of the DM laser structure, originally intended for telecommunications applications [34], together with a very narrow wavelength range, were identified as being ideal for photoacoustic swept-wavelength measurements.…”
Section: B Laser Selectionmentioning
confidence: 99%